Architectural impacts on sense of place in state mosques of Malaysia - Seyed Maziar Mazloomi, 1979-; Syed Ahmad Iskandar Syed Ariffin, supervisor; Fakulti Alam Bina (2013)
Thesis (Ph.D (Senibina)) - Universiti Teknologi Malaysia, 2013